2002
DOI: 10.1086/339692
|View full text |Cite
|
Sign up to set email alerts
|

A New Susceptibility Locus for Autosomal Dominant Pancreatic Cancer Maps to Chromosome 4q32-34

Abstract: Pancreatic cancer is the fifth leading cause of cancer death in the United States. Nearly every person diagnosed with pancreatic cancer will die from it, usually in <6 mo. Familial clustering of pancreatic cancers is commonly recognized, with an autosomal dominant inheritance pattern in approximately 10% of all cases. However, the late age at disease onset and rapid demise of affected individuals markedly hamper collection of biological samples. We report a genetic linkage scan of family X with an autosomal do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
2
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(60 citation statements)
references
References 22 publications
1
56
2
1
Order By: Relevance
“…1 Pogue-Geile et al used a two-pronged approach to discover this gene. First, they hypothesized that abnormalities in the expression of genes within the area of linkage on 4q32-34 may help localize the putative familial pancreatic cancer gene.…”
Section: Introductionmentioning
confidence: 99%
“…1 Pogue-Geile et al used a two-pronged approach to discover this gene. First, they hypothesized that abnormalities in the expression of genes within the area of linkage on 4q32-34 may help localize the putative familial pancreatic cancer gene.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, little is known about the role of these mutant genes in the development of sporadic and familial pancreatic cancer, due in part to the lack of identifiable early-stage patients. Furthermore, it is hypothesized that the major cause(s) of inherited susceptibility to pancreatic cancer remains to be identified (see, e.g., Eberle et al 2002).…”
mentioning
confidence: 99%
“…Genomewide linkage screen of a family, noted as 'family X', has shown significant linkage to chromosome 4q32-34 (Eberle et al, 2002). Pogue-Geile et al (2006) later found a mutation, inducing a proline (hydrophobic) to serine (hydrophilic) amino acid change (P239S), in a highly conserved region of the gene encoding palladin (PALLD), segregating in all affected family members and absent in unaffected family members.…”
Section: Familial Pancreatic Cancer Associated Palld Gene (Mim 164757)mentioning
confidence: 99%